2018
DOI: 10.1515/rjim-2017-0030
|View full text |Cite
|
Sign up to set email alerts
|

Left anterior descending coronary artery dissection during ventricular tachycardia ablation – case report

Abstract: Fascicular left ventricular tachycardia (VT) is the second most frequent idiopathic left VT in the setting of a structurally normal heart. Catheter ablation is curative in most patients with low complication rates. We report a case of ostial left anterior descending coronary artery (LAD) occlusion during fascicular ventricular tachycardia ablation. Dissection was the most likely cause of LAD obstruction. To the authors' best knowledge, this is the first case reporting selective LAD dissection during electrophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In total, 22 reports of severe LMCA injury related to catheter ablation have been found, ranging from 1993 to 2018 . Additionally, four reports of serious ostial or proximal LAD and Cx damage have also been identified . In this group, retrospective review of the angiograms suggested that it had been induced by a deep insertion of an ablation catheter into a short LMCA, which itself had been left unharmed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, 22 reports of severe LMCA injury related to catheter ablation have been found, ranging from 1993 to 2018 . Additionally, four reports of serious ostial or proximal LAD and Cx damage have also been identified . In this group, retrospective review of the angiograms suggested that it had been induced by a deep insertion of an ablation catheter into a short LMCA, which itself had been left unharmed.…”
Section: Resultsmentioning
confidence: 99%
“…In three cases, glycoprotein IIB/IIIA receptor antagonist abciximab (potent antiplatelet agent) was administered . In one patient with LMCA dissection, and two others with ostial LAD occlusion caused by deep LMCA penetration, aspirational thrombectomy was attempted, but no thrombus was retrieved …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The transient STE was determined to be a Brugada phenocopy during ablation of ventricular tachycardia because of coronary vasospasm of unknown etiology 18 . A case of left anterior descending coronary artery dissection during ablation of fascicular left ventricular tachycardia has been reported a swell 19 . The patient developed STE in leads V1 through V5 and the dissection was hypothesized to be because of catheter manipulation after several attempts at crossing the aortic valve.…”
Section: Reviewmentioning
confidence: 99%